2021
DOI: 10.1111/ppl.13519
|View full text |Cite
|
Sign up to set email alerts
|

Galactoglucomannan structure of Arabidopsis seed‐coat mucilage in GDP‐mannose synthesis impaired mutants

Abstract: Cell-wall polysaccharides are synthesized from nucleotide sugars by glycosyltransferases.However, in what way the level of nucleotide sugars affects the structure of the polysaccharides is not entirely clear. guanosine diphosphate (GDP)-mannose (GDP-Man) is one of the major nucleotide sugars in plants and serves as a substrate in the synthesis of mannan polysaccharides. GDP-Man is synthesized from mannose 1-phosphate and GTP by a GDP-Man pyrophosphorylase, VITAMIN C DEFECTIVE1 (VTC1), which is positively regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Its paralogous gene, At1G74910.2 (KJC1), is homologous to human GMPPA (GMP alpha subunits) and likely interacts with AtCYT1 protein to positively regulate GMP activity, thereby promoting the synthesis of GDP-D-mannose (Zheng et al, 2021). Among them, the mannose content of vct1-1 was significantly lower than that of kjc mutant (Sawake et al, 2015;Nishigaki et al, 2021), indicating that CcGMP7 and CcGMP4 had a mutually reinforcing effect, and CcGMP4 regulated mannosesynthesis in a large proportion. The GO annotation results for CcGMP7 and CcGMP4 differed in that the former lacked binding activity with organic and heterocyclic compounds, which may account for its lower expression level compared to the latter.…”
Section: Discussionmentioning
confidence: 96%
“…Its paralogous gene, At1G74910.2 (KJC1), is homologous to human GMPPA (GMP alpha subunits) and likely interacts with AtCYT1 protein to positively regulate GMP activity, thereby promoting the synthesis of GDP-D-mannose (Zheng et al, 2021). Among them, the mannose content of vct1-1 was significantly lower than that of kjc mutant (Sawake et al, 2015;Nishigaki et al, 2021), indicating that CcGMP7 and CcGMP4 had a mutually reinforcing effect, and CcGMP4 regulated mannosesynthesis in a large proportion. The GO annotation results for CcGMP7 and CcGMP4 differed in that the former lacked binding activity with organic and heterocyclic compounds, which may account for its lower expression level compared to the latter.…”
Section: Discussionmentioning
confidence: 96%
“…VITAMIN C DEFECTIVE1 (VTC1; also known as GMP1/CYT1) is the major PPase producing GDP‐Man in Arabidopsis (Table 1) and its activity is enhanced via physical interactions with the KONJAC1 (KJC1) and KJC2 protein co‐factors (Sawake et al ., 2015). Genetically reducing GDP‐Man availability in vtc1 and kjc1 mutant seeds severely reduced GGM content in Arabidopsis mucilage (Nishigaki et al ., 2021). However, the kjc1 mucilage displayed a surprisingly normal gel electrophoresis profile of GGM oligosaccharides (Fig.…”
Section: Biosynthesis Of β‐Mannan Polysaccharidesmentioning
confidence: 99%
“…The first plant GMPase gene VITAMIN C DEFECTIVE 1 ( VTC1 ) was genetically defined in the model plant Arabidopsis thaliana (Arabidopsis) by screening the vitamin C-deficient mutants ( Conklin et al, 1997 , 1999 ), and was found to be identical to the gene CYTOKINESIS DEFECTIVE1 ( Lukowitz et al, 2001 ). Studies of the Arabidopsis vtc1 mutants have revealed that VTC1 is implicated in physiological processes including cell-wall formation ( Nickle and Meinke, 1998 ; Nishigaki et al, 2021 ), cytokinesis ( Falbel et al, 2003 ), control of the transcription of defense-related and senescence-associated genes ( Pastori et al, 2003 ; Barth et al, 2004 ; Pavet et al, 2005 ), and ammonium sensitivity ( Qin et al, 2008 ; Barth et al, 2010 ). These findings reflect the diverse functions of the nucleotide sugar GDP-Man in plants ( Bar-Peled and O’Neill, 2011 ; Figueroa et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%